Sub Microsecond Analysis of Negative Cloud-To-Ground Lightning Flashes - A.I.A. Rahman; M.A. Bahari; Z.A. Baharudin; A.A. Zulkefle; M. Zainon; M.A.M. Hanafiah (Institute of Advanced Engineering and Science, 2018)
This paper expounds a development software for the identification of lightning discharge in cloud-to-ground flashes. The study was to reduce a misleading detection of the electric field radiation of a lightning discharge profile by considering the important parameters of sub microseconds structure of lightning return stroke. The software was built-in MATLAB. The development of the software considered the important parameter of return strokes such as peak value, zero crossing, rising time and fast transition time. We used a modelling technique for training and patterning the 19 return stroke from electric radiation field generated by the negative cloud-ground lightning flashes recorded in Universiti Teknikal Malaysia Melaka. The 19 return strokes data were recorded by using Lecroy HDO4024 with 5 MS/s. The results showed that the software had the ability to recognize the lightning parameters such as peak value, zero crossing, rising time and fast transition time. In conclusion, the software was able solved the uncertainty of the unknown cloud-to-ground lightning flashes parameter.